INNOVATIONS, VENTURE FINANCING AND MARKETING TECHNOLOGIES IN NEW ECONOMY - Natalia V. Przhedetskaya (Advanced Engineering Research)
Problems of the innovative-investment field in the Russian Federation at the present stage are considered. The necessity of founding venture capital funds, managing ventures companies and their participation in the knowledge economy development with a use of marketing technologies is proved. The role of the state in the venture financing and investing practice is specified.